Analysis of Improving the Efficiency and Effectiveness of Company Resource Utilization Using CPM and PERT Approaches: A Case Study - Wagimin Wagimin; Anwar Fattah (Newinera Publisher, 2026)
Effective project management is essential for technology service companies to improve resource efficiency and minimize project delays. PT XYZ has experienced an increase in project demand, but several projects have not been completed according to the planned schedule, resulting in financial losses and potential client dissatisfaction. This study aims to analyze the scheduling of the Hospital Informatics Project at PT XYZ using the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT). A descriptive quantitative case study approach was applied by identifying project activities, determining activity dependencies, allocating human resources, developing a project network, and calculating project duration and completion probability. The CPM analysis shows that the critical path of the project is C–F–H–J, with an optimal completion time of 45 months. The PERT analysis indicates that the probability of completing the project within the target duration is 24.51%. The findings also show that project delays may be influenced by work methods, environmental conditions, material availability, human resources, and extraordinary circumstances. Therefore, the integration of CPM and PERT can help PT XYZ improve project scheduling, monitor critical activities, reduce delay risks, and enhance the efficiency and effectiveness of company resources.